Impact of Service Quality and Price on Consumer Satisfaction at Indomaret. - Lasman Eddy Bachtiar; Melva Sitanggang; Ningsih Wati Simanullang (Universitas Ibn Khladun Bogor, 2024)
This research was carried out to find out the impact of quality of service and price on consumer satisfaction in Indomaret Jl. Mandala By Pass No. 170. This research uses quantitative and qualitative methods with causal associative method. In this study who became the population is the community in which once bought in Indomaret Jl. Mandala. The sampling technique is incidental because this technique is based on randomness, anyone who has a particular randomness with the researcher can be used as a sample, when viewed by the person who has been randomly found suitable for as a data source, where there are 50 samples. Data analysis techniques using validity test, reliability test, classical assumption test, double linear analysis test, t test, F test, and determination coefficient test (R2) using SPSS version 16 application. From the results of the research showed that the result of the test of the variable quality of service thitung 3,098 > tables of 1,678 then the quality of the service is influential and significant to consumer satisfaction in Indomaret Jl. Mandala By Pass No. 170 and the result from the price variable table of the price thitung 6,125 > 1,678 so the price has an influence and a significant effect on the satisfaction of the consumer in Indomaret